Theoretical and Experimental Approach for the Sensation of Urine Ubiquitin Conjugating Enzyme E2 C (UBE2C) mRNA Related to Bladder Cancer by Polyacrylamide Sensor Doped with Zinc Oxide - Asker, Noha; Gabal, Raghda Abou (Trends in Sciences, 2022)
Bladder cancer (BC) is the ninth and 4 most prevalent cancer in men worldwide and in the United States. Urothelial carcinoma (UC) is the most common histological kind. Biosensors are devices that translate complex biological events into an electrical signal whose intensity is proportional to the analyte’s concentration, allowing them to detect a specific biological analyte. The nanotechnology with nanoparticles improves and modifies the biorecognition element to improve the biosensing phenomenon, making it one of the most popular subjects among scientists. Employment of ZincOxide (ZnO) nanoparticles into the polyacrylamide (PAM) is supposed to enhance electrical and sensory capabilities that promise more inventive and faster detection with improved repeatability. Studying the ability of PAM\ZnO nanocomposite to sense Urine Ubiquitin Conjugating Enzyme E2 C (UBE2C), the nanocomposite’s interactions with the enzyme was studied using a modeling model, and then the PAM\ZnO nanocomposite was prepared and studied with spectroscopic technique. Consequently, the Fourier Transform Infrared (FTIR) spectra for PAM\ZnO resulted in peaks in the 400 - 600 cm−1 range that vanished in acidic media. Density functional theory (DFT) calculations were performed at B3LYPL using the basis set 6-31G on PAM\ZnO nanocomposites with cysteine 114. The findings of the HOMO/LUMO bandgap energy, total dipole moment (TDM), and Molecular Electrostatic Potential (MESP) indicated that the effect of ZnO in the presence of PAM gives a nanocomposite with high electronic characteristics with a TDM ranging from 5.4464 to 12.3348 Debye, and bandgap (∆E) 0.19965 to 0.28302 eV. A variation in the electrostatic characteristics of this composite followed the addition of Cystine 114. The distinctive properties of such nanocomposite PAM/ZnO enable usage in biosensor applications for bladder cancer. Finally, the FTIR spectrum showed that the estimated model fits as a proper biosensor. HIGHLIGHTS Mapping molecular electrostatic potential (MESP) maps reveal important details about the interaction, active sites, and the type of chemical addition that a molecule is most likely to go through Theoretical studies show that combining ZnO with PAM polymer is feasible, as it indicates the production of more reactive structures In terms of performance, after adding Cystine114 to PAM/ZnO polymer, electrostatics characteristics of PAM/ZnO polymer varied in acidic medium, which indicates the potentiality of the constructed Polyacrylamide sensor modified with Zinc oxide for bladder cancer GRAPHICAL ABSTRACT